Importancia de un observatorio de sostenibilidad que aporte a la gestión social y ambiental de los gobiernos autónomos descentralizados del Cantón Chimbo, 2017 - Molina Galeas, Jessenia Alexandra (2018)
The present investigation about the Importance of a Sustainability Observatory that contributes to the Social and Environmental Management of the Decentralized Autonomous Governments of Canton Chimbo, 2017, was carried out according to the research lines established in a determined time with the purpose of determining the need to implement a sustainability observatory in the canton Chimbo, which covers existing needs, in addition to providing timely information to the public. In the research process, three chapters were elaborated. The first chapter consists of the subject, the background, justification, objectives, theoretical framework, the inductive, deductive, scientific, historical-logical methods were used, the type of research is descriptive and field, the techniques applied to the Data collection were surveys and interviews. The second chapter is made up of data processing, analysis and interpretation of surveys and interviews that were conducted to managers, citizens of the canton Chimbo. The third chapter is made up of the proposal, which is to design a sustainability observatory methodology for the social and environmental management of the Decentralized Autonomous Governments of the Chimbo Canton. As a result of this investigation, we have to inform the citizenship in the Canton of Chimbo about the actions it carries out, as well as allowing citizens to contribute ideas and suggestions and thus provide solutions to the problems and needs existing in the Canton